La búsqueda de la verdad conduce al fracaso : análisis social y narratológico de ₃Quién mató a Palomino Molero? de Mario Vargas Llosa. - Abanto Rojas, Luis A. (University of Ottawa (Canada), 1996)
quesQuien mato a Palomino Molero? (1986) has received little attention by critics and scholars. What criticism does exist contributes to a panoramic, and in certain cases, fragmentary view of the novel, but little to an understanding of its deep structure, narrative functioning and content. This thesis attempts to fill the gap in existing critical approaches by proposing a new reading based on a reassessment of the author's conception of literary creativity (chapter I), an analysis of the detective genre and its use by the author to illustrate the socio-political condition of Peruvian reality (chapters II and III), and an examination of the novel's narrative functioning from a narratological perspective (chapter IV). The main conclusions of my study are as follows: First, Vargas Llosa, in this work, takes his personal experiences as the stimulus and substance (he calls them "the demons") for the novel's story and problematics. Second, both partially in adopting and transgressing the detective story structure, the author efficiently projects that story and the economic realities of the 1950s. Third, the world-vision that thus emerges is one of a society deeply fractured and divided. Fourth, in the case of quesQuien mato a Palomino Molero?, this world-vision is mainly conveyed through the focalization of the character-focalizer Lituma, and the appropriate use of a privileged, heterodiegetic narrator, mimetic discourse, and indirect free discourse. Fifth, both the adoption and the transgressions of the detective story structure, as well as the narratological components efficiently articulate the expression of the aforementioned world-vision by the implied author. quesQuien mato a Palomino Molero? thus constitutes a meaningful quest novel that convincingly shows that, in the world presented, all quest for truth by the underprivileged sectors of society, whenever it jeopardizes the interest of the privileged ones, inevitably ends in failure. (Abstract shortened by UMI.)
Keywords: Literature, Modern.